SOCIO-ECONOMIC CONDITIONS OF HOUSEHOLD RUBBER FARMER IN PASARBARU VILLAGE PANGEAN SUBDISTRICT KUANTAN SINGINGI DISTRICT - DASRIYANTO, DASRIYANTO; Keslan, S.Si., M.Si,, Widya Prari; Despica, S.Pd., M.Si, Rika Despica, S.Pd., M.Si (STKIP PGRI Sumbar, 2014)
ABSTRACKÂ Â Â Â Â Â Â Â Â Â Â Â The phenomena of rubberâs production infact that the rubberâs production in 2009, 2010, and 2011 had decreased of every years and was giving an impact to the economic system of farmerâs in Pasarbaru Pangean villlage, Pangean subdistrict, Kuantan Singingi district. The purpose of this vesearch is to analyze 1) The full fillment of basic needed of rubberâs farmer (basic, conventional need, clothing). In Pasarbaru village Pangean subdistrict Kuantan Singingi district, 2) the rubberâs farmerâs work experience in Pasarbaru village Pangean subdistrict Kuantan Singingi district, 3) the rubberâs farmerâs income in Pasarbaru village Pangean subdistrict Kuantan Singingi district. The result of this research are 1) basic needed of food basic neded is rice (100%), basic food as tofu and tempe (42%), and the cost of basic needed for 1 day is < Rp. 100.000 (69,6%), then for clothâs rubberâs farmerâs is bought once for every six month (49,3%), and outcome for every year is Rp. 500.000-1.000.000 (40,6%), confentional needed is seen by the type of house a half complete and complete (43,5%), the wide of that house is 7x9 meters (33,3%). 2) work experience based on the level of knowledge of rubbers farmers (49,3%) and the last graduated of rubbers farmers is elementary school (46,4%), the time of the are spend to take the rubbers is about 7 hours (34,8%), their skill can see from the experience as a rubbers farmer is from self taught (37,7%). 3) the income from the wide of rubber land is about Rp. 1.000.000 (50,7%), and a little incoming from rubbers land when rainy season (27,5%).